Pengaruh Konsep Diri dan Dukungan Sosial Terhadap Body Image pada Remaja Perempuan di Karawang - Nurbaeti; Cempaka Putrie Dimala; Haryanti Mustika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Teenage girls are vulnerable to body dissatisfaction due to beauty standards shaped by the media and social environment. The purpose of this study is to determine the influence of self-concept and social support on body image among teenage girls in Karawang, as well as the simultaneous influence of both on body image among teenage girls in Karawang. The research method used a quantitative approach with a causal design. The sample consisted of 348 adolescent female respondents obtained through non-probability sampling using incidental sampling. The research instruments included the Self-Concept Scale to measure self-concept, the Multidimensional Scale of Perceived Social Support (MSPSS) to measure social support, and the Body Image Scale to measure body image. All instruments underwent validity and reliability testing with satisfactory results. Data analysis was conducted using multiple linear regression analysis with the SPSS program. The results of the study indicate that there is a significant influence of self-concept on body image, a significant influence of social support on body image, and a significant simultaneous influence of self-concept and social support on body image among adolescent girls in Karawang.